2008
DOI: 10.1007/s10974-008-9156-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fast skeletal muscle activity by SERCA1 vicinal-cysteines

Abstract: During prolonged skeletal muscle contractions free radicals are produced that may lead to fatigue. Vicinal cysteines, known as a Vicinal-thiol groups react preferentially among them depending on redox potential. Therefore, we examined the role of VT groups on the activity and conformational changes of sarcoplasmic reticulum (SR) Ca(2+)-ATPase (SERCA1) from rabbit skeletal muscle isolated SR, by selective oxidation-reduction of VT-groups. After Ca(2+) is released from the SR to start contraction, SERCA1 pumps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Because MβCD is not membrane-permeable, the effect observed on the muscle force is related to the reduction of the cholesterol concentration in surface membranes. During tetanic contraction, the SR is depleted of calcium and does not have time to recover due to the reduced activity of the SR calcium pump (SERCA1), which leads to muscle fatigue [50]. Based on the results shown in Fig.…”
Section: Mechanical Properties Of Fast Skeletal Muscle Partially Deplmentioning
confidence: 99%
“…Because MβCD is not membrane-permeable, the effect observed on the muscle force is related to the reduction of the cholesterol concentration in surface membranes. During tetanic contraction, the SR is depleted of calcium and does not have time to recover due to the reduced activity of the SR calcium pump (SERCA1), which leads to muscle fatigue [50]. Based on the results shown in Fig.…”
Section: Mechanical Properties Of Fast Skeletal Muscle Partially Deplmentioning
confidence: 99%
“…Dysregulated calcium homeostasis through free radical‐mediated oxidation of thiols has been implicated in muscle fatigue 50. Oxidation of vicinal (adjacent) cysteines of sarcoplasmic reticulum Ca(2+)‐ATPase (SERCA1) under conditions that simulate titanic stimulation induced muscle fatigue has also been suggested 75.…”
Section: Nutritional Myopathy and Ataxia In Animal Models Of Dietarmentioning
confidence: 99%
“…Transition A corresponded to the denaturation of the nucleotide-binding domain (NBD), and transition B corresponded to the denaturation of the transmembrane Ca 2+ -binding domain (CBD) [21,24]. Several pieces of evidence demonstrated that conformational changes in SERCA1 induced by the presence of SERCA1 inhibitors such as the calcium channel blocker D-600 [24] or redox modification through SERCA1 vicinal thiol oxidation [25] and biological conditions that modify SERCA1 activity such as changes during muscle fatigue or muscle adaptation to exercise [25,26] are reflected by changes in the SERCA1 conformations revealed by modification on the SERCA1 thermodynamic parameters obtained from thermal denaturation (DSC). Fig.…”
Section: Resultsmentioning
confidence: 99%